Механізми формування громадської думки в умовах глобального розвитку - Кіоссе, Лідія Михайлівна; Киоссе, Лидия Михайловна; Kiosse, Lidiya M. (My University, 2015)
Дисертація на здобуття наукового ступеня кандидата політичних наук за спеціальністю 23.00.04 - політичні проблеми міжнародних систем та глобального розвитку. - Національний університет «Одеська юридична академія», Одеса, 2015. У дисертації здійснено комплексне дослідження механізмів формування громадської думки в умовах глобального розвитку, проаналізовано технологічні, інституційні та функціональні особливості формування громадської думки епохи глобалізації. У межах здійсненого дослідження були отримані результати, що мають наукову новизну, обумовлену вирішенням актуальних проблем формування громадської думки в умовах глобального розвитку, які не отримали достатньої розробки у науковій літературі. Визначено механізми формування громадської думки в умовах сучасного політичного розвитку крізь призму комплексного аналізу глобалізації, яка найбільш рельєфно проявляється у сфері політичної взаємодії між державною владою, інститутами громадянського суспільства та наднаціональними політичними та економічними структурами, а також вплив глобалізації на формування громадської думки. Обґрунтовано специфіку впливу глобалізації на трансформації механізмів формування громадської думки. Визначено, що саме як наслідок глобалізаційних процесів у політичній, економічній, культурній сферах відбуваються зміни у світогляді громадян різних країн, утворюється феномен глобальної громадської думки, що базується на постмодерних інтерпретаціях політики, постматеріальних цінностях та використанні глобальних комунікативних мереж.

Диссертация на соискание ученой степени кандидата политических наук по специальности 23.00.04 - политические проблемы международных систем и глобального развития. — Национальный университет «Одесская юридическая академия», Одесса, 2015. В диссертации осуществлено комплексное исследование механизмов формирования общественного мнения в условиях . глобального развития, проанализированы технологические, институциональные и функциональные особенности формирования общественной мысли эпохи глобализации. В рамках проведенного исследования были получены результаты, имеющие научную новизну, обусловленную решением актуальных проблем формирования общественного мнения в условиях глобального развития, которые не получили достаточной разработки в научной литературе. Определены механизмы формирования общественного мнения в условиях современного политического развития сквозь призму комплексного анализа глобализации, наиболее рельефно проявляется в сфере политического взаимодействия между государственной властью, институтами гражданского общества и наднациональными политическими и экономическими структурами, а также влияние глобализации на формирование общественного мнения. Обоснованно специфику влияния глобализации на трансформации механизмов формирования общественного мнения. Определено, что именно вследствие глобализационных процессов в политической, экономической, культурной сферах происходят изменения в мировоззрении граждан разных стран, образуется феномен глобальной общественного мнения, основанного на постмодернистских интерпретациях политики, постматериальных ценностях и использовании глобальных коммуникативных сетей.

Thesis for the degree of candidate of political sciences, specialty 23.00.04 - political problems of international systems and global development. - National University «Odessa Law Academy», Odesa. 2015. The dissertation presents a comprehensive study of the mechanisms of formation of public opinion in terms of global development, analyzed the technological, institutional and functional features of the formation of social thought the era of globalization. As part of the study, results were obtained with scientific novelty due to solving actual problems of the formation of public opinion in terms of global development, which have not received sufficient development in the scientific literature. The mechanisms of formation of public opinion in the present political development in the light of the complex analysis of globalization, which is most clearly manifested in political cooperation between public authorities, civil society and supranational political and economic structures and the impact of globalization on public opinion. Reasonable specificity the impact of globalization on the transformation of the mechanisms of formation of public opinion. Determined that it is due to globalization processes in the political, economic and cultural spheres is a change in the outlook of different nationalities, the phenomena of global public opinion, based on the post-modern interpretations of policy postmaterial value and use of global communication networks. The basic technology of the formation of public opinion in the context of globalization. On the one hand, it is the unification of the space of political and socio-cultural identity under the influence of globalization and global public opinion, there is in the «core» of the world system, its extension to the countries of the «semi-peripheiy» and «periphery». On the other hand, the formation of alternative political and social movements, representatives of which proclaim the priority and protection of national and local cultures, values and traditions, historical heritage, as well as exacerbation of ethno-political, religious, gender, social and environmental conflicts at the national and regional levels. Substantiates the role of globalization processes in the formation of public opinion under the influence of information networks and technologies of coverage policies and activities of the new (alternative) organizations, movements and subcultures, which are sent to the expression in the public opinion of political, social, economic, environmental, cultural forms of organization of modern society in terms of global development. Argued that the development of mechanisms for the formation of public opinion occurs in such measurements political interaction as vertical and horizontal organization policy, rationalization and irratsionalizatsiey political interaction, marketization policies, political culture and political values, the development of political communication, the level of political participation and citizen participation. Factors influencing public opinion in the global development attributed postmaterial value system, shift of attention to personal fulfillment, social inclusion, the need for recognition from the community, decentralization of political organizations and their activities on the basis of the network. Determined that in the process of shaping public opinion indoctrination occurs sphere of values, the convergence of cultural, political, and social capital. Reasonable understanding of glocalization as the interaction of globalization processes in politics, economics and culture, and the simultaneous development of local cultures and communities, affect the transformation of public opinion. The factors of influence on the glocalization mechanisms of public opinion, which are due to the peculiarities of the social and economic development of the regions, as well as local traditions, culture, development of scientific and educational institutions, religious orientation of citizens and others. Noted that the special role of the communicative component of the process of opposition activity, constructed during the interaction with the authorities, associations, media and political parties in the horizontal and vertical dimensions of political interaction. It is proved that the basis of the political opposition is not only the interaction with the government, and relations with informed citizens, social groups and society as a whole. The emphasis is on the fact that in the present conditions of the opposition and the public relations indirect information space, in particular - the activities of the mass media.
Кіоссе Л. М. Механізми формування громадської думки в умовах глобального розвитку : автореф. дис. ... канд. політ. наук : 23.00.04 / Л. М. Кіоссе; кер. роботи Д. В. Яковлев; Нац. ун.-т "Одеська юридична академія". – Одеса, 2015. – 19 с.
Keywords: громадська думка; глобальний розвиток; комунікативність; міжнародні інституції; глобальна громадська думка; глокалізація; політична трансформація; інститут громадянського суспільства; общественное мнение; глобальное развитие; коммуникативность; международные институции; глобальная общественное мнение; глокализация; политическая трансформация; институт гражданского общества; public opinion; global development; communicative; international institutions; global public opinion; glocalization; political transformation; institute of civil society